Role of Interferons in the Development of Diagnostics, Vaccines, and Therapy for Tuberculosis - Kai, Ling Chin; Zulkipli Anis, Fadhilah; Sarmiento, Maria E.; Norazmi, Mohd Nor; Acosta, Armando (Hindawi Publishing Corporation, 2017)
Tuberculosis (TB) is an airborne infection caused by Mycobacterium tuberculosis (Mtb). About one-third of the world’s population is latently infected with TB and 5–15% of them will develop active TB in their lifetime. It is estimated that each case of active TB may cause 10–20 new infections. Host immune response to Mtb is influenced by interferon- (IFN-) signaling pathways, particularly by type I and type II interferons (IFNs). The latter that consists of IFN-γ has been associated with the promotion of Th1 immune response which is associated with protection against TB. Although this aspect remains controversial at present due to the lack of established correlates of protection, currently, there are different prophylactic, diagnostic, and immunotherapeutic approaches in which IFNs play an important role. This review summarizes the main aspects related with the biology of IFNs, mainly associated with TB, as well as presents the main applications of these cytokines related to prophylaxis, diagnosis, and immunotherapy of TB.